The use of ICT in the teaching and learning process in secondary schools : a case study of two Cameroonian schools - Kennah, Mua (2016)
Abstract The Use of ICT in the Teaching and Learning Process in Secondary Schools: A Case Study of Two Cameroonian schools. This study examines the use of ICT by teachers Cameroonian secondary schools. This study explores the pedagogical use of ICT in the teaching and the learning process, the impact of its use and the role school principals and the community plays in enhancing ICT in the pedagogy. This is a qualitative case study of two public secondary schools in the South West Region of Cameroon consisting of interviews and observations. A total of 24 participants comprising of 20 teachers, two school principals and two parents responded to semi-structured interview questions. Also, observational study was also carried out to examine the various pedagogical practices of ICT in both schools. All the interview data were all transcribed and interpreted using the participants’ quotes as examples and evidence of the findings. Pictures were used to analyse observational data whereby moments related to the pedagogic use of ICT in the classroom and other areas in the schools under study were captured and described to strengthen the findings. The TPACK model was used to examine the teacher's knowledge in the pedagogic use of ICT Findings in this study indicated that pedagogic use of ICT is still in its preliminary stages as 16 out of the 20 teachers were passively using ICT in their classroom and an additional two teachers were non-users of ICT in their pedagogic activities.Also, there were no significant changes in the teachers’ position as a result of the pedagogic use of ICT in the classrooms. 2 out of the 18 teachers who considered themselves as active pedagogic users of ICT were still using the traditional instructional method of teaching even though ICT tools were present in the classrooms. Inadequate ICT training for teachers in their subject area acted as a major challenge for teachers from both schools to integrate ICT in their subject areas. Therefore ICT was still used as an add-on rather than an integrated tool in the teaching and learning process. The majority of the teachers acknowledge positive changes ICT had left in the teaching and learning process. Also, findings from this study reveal that the school principals and parents had little influence over the use of ICT in the pedagogy. It is evident from this study that for teachers to successfully integrate ICT in their classrooms, the teacher pre-service and in-service courses have to technologically drive to ensure effective use of ICT in the pedagogy.